Using of electron cyclotron resonance discharge in ion beam sputtering systems for space charge compensation - Bizyukov, A.A.; Tarasov, I.K.; Chibisov, A.D. (Вопросы атомной науки и техники, 2019)
The possibility of using a magnetic mirror in the output gap of ion source with a closed electron drift to generating of an additional gas discharge by using the electron-cyclotron resonance to compensate of the ion beam space charge is studied. The first experiments have shown that an additional microwave discharge generated in the region of the annular gap when the microwave power is applied. An additional plasma source of electrons provides the maintenance and intensification of the gas discharge in the accelerator with an anode layer.